COMPARISON STUDY OF COMPRESSIVE STRENGTH OF RED BRICKS AND LIGHT BRICKS - Mohammad Djaelani; Didit Darmawan (Jurnal Ilmiah Satyagraha, 2022)
The progress of development in Indonesia is very rapid, buildingmaterials are demanded to have very good quality. The purpose of this study is todetermine the comparison of the compressive strength of red brick andlightweight brick as it should be in the field of development that affects economicdevelopment, in this study it is very useful for the community when buyingmaterials. This type of research is qualitative. The data was obtained byconducting research on data analysis techniques. used is to use a formula todetermine the value of compressive strength. The results showed that red bricksand light bricks had different compressive strength values. Lightweight brickswhich are heated in the sun for 7 days have a compressive strength value of58.916 kg/cm², while those that are soaked in water for 4 days have a compressivestrength value of 36.256 kg/cm² and those which are blown in the wind for 28days have a compressive strength value of 45.32 kg/cm². cm². for red bricks thatare dried for 5 days and then burned for 1 day. after the red bricks are ripe andthen heated in the sun for 7 days has a compressive strength value of 33,709kg/cm² while those that are soaked for 4 days have a compressive strength valueof 29,495 kg/cm² and those that are ventilated for 28 days have a compressive strength value of 25,281 kg/cm².